O texto do intérprete de libras no contexto do bilingüismo eo pretexto da inclusão - Costa, Karla Patrícia Ramos da (2008)
This work deals with the performance of the Brazilian Sign Language (LIBRAS) interpreter s actuation in an inclusive educational context, adopted in Brazil, due to the necessity of better knowing the results of this professional s participation in the school and social life of a deaf person. The great remarkable question pointed out is if this presence favors the deaf person s development and which demands are necessary for his interpretative effectiveness. Interpreting corresponds to a cognitive process in which messages from one language to another are exchanged (oral or sign). At the same time it represents a syntax, semantics and pragmatic decision making in two languages which always requires new interpretations. So, the interpreter does not need to be a mere explainer, but a bilingual professional, qualified for translating sign language (LIBRAS) into Portuguese. This work has been developed aiming at analyzing sign language (LIBRAS) interpreters reports regarding their contributions in order to improve the interaction between deaf people and listeners. In this sense, a qualitative methodology was used and as a research tool we selected an interview that provided reports from 10 (ten) sign language (LIBRAS) interpreters of public elementary II and high schools in Recife (which represents over 70% total). The data provided through the reports were classified and then analyzed based on the chosen theoretical frame of references. The professionals who were interviewed stated that they were satisfied with their work, although they admit there are several obstacles to overcome (which not always are). According to them, the interpreter s work lacks a better infrastructure than the one we have nowadays which demands actions that are already part of the public policies and that up to now haven t been implemented. We hope this work will contribute to help improve the performance of these professionals, since they have been forgotten and kept aside from who felt the necessity to count on someone who could facilitate communication among deaf and listeners